METHODS OF DETERMINING THE INTEGRATIVE CREATIVITY OF SOCIO-HUMANITARIAN TEACHERS - Jumaniyozova Mukhayo Tajievna, (EPRA International Journal of Research and Development (IJRD), 2022)
This article argues methods for determining and assessing the professional creativity of teachers, characteristics of creative skills, criteria for professional creativity, outcomes as well as analysis of scientific research in this field.